The Efficacy of Short-Duration Polyethylene Glycol plus Electrolytes for Improving Bowel Preparation of Colonoscopy in Patients with Chronic Constipation. (24th November 2020) - Yoshida, Naohisa; Inagaki, Yoshikazu; Fukumoto, Kohei; Yoriki, Hiroyuki; Inada, Yutaka; Murakami, Takaaki; Tomita, Yuri; Hashimoto, Hikaru; Sugino, Satoshi; Hirose, Ryohei; Dohi, Osamu; Inoue, Ken; et al.
Abstract : Backgrounds and Aims . Sachets of polyethylene glycol plus electrolytes (PEG+E: Movicol: EA Pharma, Tokyo, Japan) are used for chronic constipation, and its efficacy is reported only for female and nonelderly people. Chronic constipation is one of the reasons of poor colonoscopic bowel preparation (BP). We analyzed its efficacy in improving chronic constipation and poor colonoscopic BP related to it, including male and elderly people. Materials and Methods . This multicenter retrospective study was conducted from September 2019 to September 2020 at 5 related institutions among patients ≥ 20 years old diagnosed with chronic constipation whose previous colonoscopic BP had had a fair or poor Aronchick score. Two or four sachets of PEG+E (13.7 or 27.4 g/day) were prescribed for 1 week before colonoscopy. We analyzed the rate of improvement in BP, effect-related factors, spontaneous bowel movements (SBMs), stool consistency, improvement of constipation symptoms, and adverse events. Results . We evaluated 106 cases (56 males) with an average age of 69.5 ± 9.4 years old (≤74 years old: 68 cases, ≥75 years old: 38 cases). The improvement rate of BP was 72.6%, and the insertion time and pain score also improved. A performance status of 1 or 2 was associated with poor BP. SBMs (times/week) increased from 4.0 ± 1.9 to 6.1 ± 2.6 (p < 0.001 ). The overall improvement rates of SBMs, stool consistency, symptoms of constipation, and rate of adverse events were 58.5%, 90.6%, 59.4%, and 6.6%, respectively, showing no significant differences with regard to age or gender. Conclusions . Short-duration PEG+E was effective for improving poor BP and chronic constipation.